Nonlinear Ion-Acoustic Solitary Waves in a Weakly Relativistic Electron-Positron-Ion Plasma with Relativistic Electron and Positron Beams - Barman, Satyendra Nath; Talukdar, Kingkar (East European Journal of Physics, 2024)
In this investigation, compressive and rarefactive solitons are demonstrated to exist in a plasma model that includes unmagnetized weak-relativistic positive ions, negative ions, electrons, electron beam and positron beam. For these weakly relativistic non-linear ion-acoustic waves in unmagnetized plasma with electron inertia and relativistic beam, the existence of compressive and rarefactive soliton is investigated by deriving the Korteweg-de Vries (KdV) equation. It has been observed that the amplitude and width of compressive and rarefactive solitons vary differently in response to pressure variation and the presence of electron inertia. The research determines the requirements that must be met for the existence of the nonlinear ion-acoustic solitons. The fluid equations of motion governing the one-dimensional plasma serve as the foundation for the analysis. Various relational forms of the strength parameter (ε) are chosen to stretch the space and time variables, leading to a variety of nonlinearities. The findings can have implications not only for astrophysical plasmas but also for inertial confinement fusion plasmas.